A 6000-km-long Neo-Tethyan arc system with coherent magmatic flare-ups and lulls in South Asia - Zhang, Xiaoran; Chung, Sun-Lin; Lai, Yu-Ming; Ghani, Azman Abd; Murtadha, Sayed; Lee, Hao-Yang; Hsu, Chun-Chieh (Geological Society of America, 2019)
Magmatic arcs typically exhibit non-steady-state evolution with episodic flare-ups and lulls, yet the main drivers remain contentious. Situated in the southwest margin of Southeast Asia, Sumatra records a long-lived magmatic arc that is still poorly constrained in age and tempo. Detrital zircon data from Sumatra delineate major arc magmatic pulses at ca. 212, 102-85, 52, and 22-11 Ma. The mid-Cretaceous to early Eocene zircons mostly yield high positive εHf(t) values, indicating magma derivation from juvenile sources and matching well with those of the Gangdese batholiths in the southern Lhasa terrane. These similarities substantiate an extended (~6000 km) Neo-Tethyan arc system from southern Tibet to Sumatra that exhibits concurrent magmatic lulls (ca. 150-105 and 85-65 Ma) and flare-ups (ca. 105-85 and 65-40 Ma). The Late Cretaceous magmatic lull coincided with a period of strong regional deformation and increasingly fast northward drift of India, likely attributable to Neo-Tethyan flat slab subduction. Periodic pulses of Neo-Tethyan arc magmatism most likely correlated with repeated steepening and shallowing of slab dip, rather than India-Eurasia convergence rates.